Antiproliferative activity and chemical composition of aqueous extracts and essential oil of inflorescences of Lavandula dentata L. And Lavandula angustifolia Mill - Frescura, Viviane; Trapp, Kássia Cauana; Coelho, Ana Paula Durand; Mambri, Ana Paula de Souza; Boligon, Aline Augusti; Andriolo, Jeronimo Luiz; Dail Laughinghouse IV, Haywood; Tedesco, Solange Bosio (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
The objective of this work was to determine and quantify the phenolic compounds present in extracts of Lavandula angustifolia Mill. and Lavandula dentata L. essential oils. Additionally, cytotoxicity of extracts and essential oils of these species was evaluated using the Allium cepa test. The inflorescences of 10 L. dentata and L. angustifolia plants were collected, of which aqueous extracts were prepared at concentrations of 5 and 20 g. L-1 and the essential oil was extracted. The essential oil was assessed for chemical composition through Gas Chromatography with a flame ionization detector coupled to mass spectrometry. The essential oil was diluted to obtain oil at a concentration of 0.3 %, which was used in the A. cepa test. Despite the variations between species with respect to the compounds found, there were no differences between their effects on the A. cepa test. Infusions in both concentrations and essential oil haven’t genotoxicity.